Midwifery Care in Pregnant Women with Mild Anemia - Dina Rosidatul Husna; Desy Dwi Cahyani; Finta isti kundarti (Health and Technology Journal (HTechJ), 2025)
Anemia in pregnant women is a global and national problem that can increase the risk of maternal and infant morbidity and mortality. Anemia in pregnancy is a decrease in the capacity of blood to carry oxygen caused by a decrease in the number of red blood cells or a reduced hemoglobin concentration in the blood circulation. This study aims to analyze midwifery care in pregnant women with mild anemia. This study used a case study design with a comprehensive midwifery care approach in one patient. Data were collected through interviews, observations, physical examinations, and documentation studies. Data were analyzed using the stages of the midwifery process, which include assessment, diagnosis, intervention, implementation, and evaluation. The case study was conducted on Mrs. FF, who had a hemoglobin level of 10.2 gr/dL. The diagnosis was made G1P0000, gestational age 29-30 weeks, with mild anemia of an intrauterine live fetus. The intervention was carried out by educating about the importance of iron-rich nutrition, giving oral supplementation according to the recommended dose, and monitoring hemoglobin levels. The evaluation showed an increase in hemoglobin level to 11.2 gl/Dl after 8 weeks of intervention, with clinical improvement. This case demonstrates the importance of early detection of anemia in pregnancy and appropriate management through education, supplementation, and regular monitoring. A collaborative approach between health workers and pregnant women is essential to prevent anemia-related maternal and fetal complications.